Reactive oxygen species and endurance training-induced adaptations - Hideki Matoba (Japanese Society of Physical Fitness and Sports Medicine, 2013)
Endurance training induces mitochondrial biogenesis and angiogenesis in skeletal muscle. Endurance training also improves insulin sensitivity at both the skeletal muscle and whole body level. Recently, ROS have been suggested to play an important role in endurance training-induced adaptations. However, this hypothesis is not yet fully supported. To advance understanding of the role of ROS and antioxidants in endurance training-induced adaptations, efforts should be made in future studies to clarify the sites of ROS production and the influence of antioxidants on the redox status under each training condition. Effort should also be directed to identifying the signaling pathways involved. In this situation, it should be recognized that in vivo cellular signaling is redundant. Therefore, efforts to evaluate the relative importance and interactions among the multiple cellular signaling pathways involved in each training condition are required. Without elucidating the role of ROS and antioxidants in endurance training-induced adaptations, then evidence-based sound advice regarding antioxidant supplementation cannot be made.